1978
DOI: 10.1002/1520-6807(197807)15:3<446::aid-pits2310150326>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of test anxiety on performance, worry, and emotionality in naturally occurring exams

Abstract: Test performance and reported anxiety levels of high and low test-anxious subjects taking either a regular exam or an exam containing brief, written relaxation instructions were compared. A consistent main effect for test anxiety was found; high test-anxious subjects performed more poorly and reported greater worry and emotionality than did low test-anxious subjects. Effects for the relaxation manipulation were found only on the second of three exams where the high anxious subjects receiving the relaxation exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

1984
1984
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…Research has demonstrated that the performance-debilitating effects of anxiety are specifically related to the worry component, whereas the emotionality component is unrelated to performance decrements (Deffenbacher, 1980;Tyron, 1980). Similarly, research by Deffenbacher and Deitz (1978) has suggested that cognitive interference is the key predictor of performance deficits (see Sarason, 1984, for similar findings).…”
Section: Anxietymentioning
confidence: 97%
“…Research has demonstrated that the performance-debilitating effects of anxiety are specifically related to the worry component, whereas the emotionality component is unrelated to performance decrements (Deffenbacher, 1980;Tyron, 1980). Similarly, research by Deffenbacher and Deitz (1978) has suggested that cognitive interference is the key predictor of performance deficits (see Sarason, 1984, for similar findings).…”
Section: Anxietymentioning
confidence: 97%
“…As such, test‐anxious students often receive insufficient attention, and the deleterious effects of test anxiety are often underestimated (see Fehm & Fydrich, ; Jürgens, ; Zuriff, ). Numerous studies have demonstrated that test anxiety has a severely negative impact on scholastic motivation (Deci & Ryan, ; Elliot & McGregor, ), academic performance (Buchwald, ; Cassady & Johnson, ; Deffenbacher & Deitz, , Pekrun, ), well‐being (Pekrun, ; Seiffge‐Krenke, ), and may lead to social isolation (Eum & Rice, ; Somersalo, ; Wood, ), higher rates of psychopathology (Bodas & Ollendick, ; King, Mietz, Tinney, & Ollendick, ), and early school dropout, as well as jeopardize further career plans (Cortina, ). Given these grave consequences, a better understanding of the phenomenon is imperative.…”
mentioning
confidence: 99%
“…Thus, it was introduced as an effect of test anxiety (Deffenbacher and Deitz, 1978;Wine, 1971) and was hypothesised to be the factor that resulted in impaired performance. Indeed, research in educational settings has supported the relationship between test anxiety and cognitive interference (e.g.…”
mentioning
confidence: 99%